Knowledge and Attitudes Relating to Barotrauma Incidents, Fishermen Communities in Buko Village, Banggai District, Central Sulawesi Islands - Yulianus Sudarnan; H. Melangka (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding begins within one hour after birth until the baby is six months old. Early initiation of Diving is a technique that is often carried out by fishermen in Batangono village with traditional techniques without using tools, from their knowledge that diving is obtained from generation to generation so that the consequences of diving activities have an impact on health, and the attitude shown in the Barotroma incident is also still lacking in handling. The aim of the research is to know the relationship between knowledge and attitudes, the incidence of Barotrauma in the community in Batangono Village, Buko District, Banggai Islands Regency. This research method uses a cross sectional approach. A sample of 42 respondents was selected from the Islands using proposive sampling. Data collection was carried out in January 2023. Data analysis used the Mann Whitney test. The results of this study show that the incidence of barotrauma is 68.4%. The results of the analysis show that there is a relationship between knowledge and events of barotrauma in the community with a p-value = 0.05. The attitude variable obtained a p-value = 0.02, meaning that there is a relationship between attitude and barotrauma events in society. The conclusion is that there is a significant relationship between knowledge and attitudes with the incidence of barotrauma in the community, suggestions for standard diving procedures to prevent barotrauma, and health agencies play a role in disseminating information about diving health.